Design of a semantic person-oriented nurse call management system. (1st December 2008) - Ongenae, F.; Strobbe, M.; Hollez, J.; De Jans, G.; Turck, F.; Dhaene, T.; Demeester, P.; Verhoeve, P.
Context information is becoming increasingly important in a world with more and more wireless devices that have to be in touch with the environment around them. In this paper, we focus on how this context information can be efficiently modelled by employing an ontology. This ontology can then be used by reasoning algorithms (e.g., Rules) which are based on this context information. This way, the algorithm is more sensitive to the varying conditions of the environment. This is illustrated with a use case which studies the transition from a place-oriented to a person-oriented nurse call system. The Context-aware Service Platform (CASP) context framework (Strobbe et al., 2007; 2006) was extended to implement the use case. A web service interface was designed which allows the insertion or extraction of new information into the Knowledge Base. Finally, a simulation was set up to illustrate the advantages and the performance of the new person-oriented approach.